Co-occurrence of Dermatomyositis and Polycythemia Unveiling Rare de Novo Neuroendocrine Prostate Tumor - Papagoras, Charalampos; Arelaki, Stella; Botis, Ioannis; Chrysafis, Ioannis; Giannopoulos, Stavros; Skendros, Panagiotis (Frontiers in Oncology, 2018)
We present a case of dermatomyositis together with polycythemia as initial manifestations of a particularly rare type of prostate cancer. A 69-year-old man was hospitalized for facial erythema and symptoms of fatigue. Physical evaluation, serum creatinine phosphokinase and electromyography were consistent with dermatomyositis. In parallel, the hemoglobin level was 18.5 g/dL, serum erythropoietin levels were low normal and no JAK2 mutation was found. Given a strong suspicion of a paraneoplastic syndrome the patient underwent abdominal computed tomography revealing a prostate mass, enlarged iliac lymph nodes and a fracture of L1 due to metastasis. The unusual paraneoplastic manifestations prompted a more thorough immunohistologic examination of the needle biopsy specimen taken from the prostate, which led to the diagnosis of large cell neuroendocrine prostate carcinoma. It is a most rare type of prostate cancer, carrying a poor prognosis. To our knowledge, this is the first case in the literature associating a neuroendocrine cancer of the prostate with dermatomyositis.